A Comparison of The Use of Wordwall and Flashcard Media on The Learning Interest and Outcomes of Elementary Students Arabic Learning at SDIT Plus Qurthuba Makassar - Indah Sari; Haniah Haniah; Rappe Rappe (Abjadia : International Journal of Education, 2026)
This research is motivated by the importance of selecting and utilizing instructional media to improve the quality of Arabic language learning, particularly in terms of students’ learning interest and outcomes. The objectives of this study are: (1) to analyze students’ interest and achievement in learning Arabic when taught using Wordwall media and flashcard media, (2) to compare the differences in interest and learning outcomes between students taught with Wordwall and those taught with flashcards, and (3) to examine the effect of Wordwall and flashcards on learning outcomes through learning interest as an intervening variable. This study employed a quantitative approach with a quasi-experimental design, specifically a comparison group post-test only design. The population consisted of all third-grade students at SDIT Plus Qurthuba Makassar, totaling 103 students, with the sample selected using purposive sampling. The research instruments included questionnaires, achievement tests, observation sheets, and documentation. Data were analyzed using descriptive and inferential statistics. The results showed that there was no significant difference in learning interest between students taught using Wordwall media and those taught using card media (p = 0.497 > 0.05), with mean scores of 83.85 in the Wordwall group and 87.75 in the card group. Similarly, there was no significant difference in learning outcomes (p = 0.522 > 0.05), with mean scores of 84.33 in the Wordwall group and 85.38 in the card group. Furthermore, learning media had no significant effect on learning outcomes (β = -0.044; p = 0.725). In contrast, learning interest was found to have a positive and significant effect on learning outcomes (β = 0.483; p < 0.01). The implications of this study indicate that improvements in learning outcomes are more influenced by internal factors, particularly students’ learning interest, rather than the type of learning media used. Therefore, teachers are encouraged to focus more on instructional strategies that enhance students’ interest and motivation in learning, rather than merely varying instructional media.